The Structure of Output of Individual Farms in Poland and in the Countries of EU-27 – An Analysis of Similarities in 2007 - Ryś-Jurek, Roma (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2010)
The aim of the conducted research was to compare the structure of agricultural output of an average Polish individual farm with that of an average farm from the EU-27 countries. The FADN data for 2007 was used for the purpose of analysis. Descriptive and comparative analyses were applied, and also some selected descriptive statistical methods were used (intensity and structure indexes, measure of structure similarity, standardization of simple characteristics and hierarchical agglomeration classification). The comparison of the principal average results of Polish and EU farms showed that the value of the greater part of these categories was lower by about a half in the average Polish individual farm than in the average EU farm. In three rankings according to the absolute values of total output, of plant production and animal production, the average Polish farm placed at the bottom of the list of 26 other average EU farms. The results obtained with the help of the measure of structure similarity proved that the structure of total output of the average Polish farm was typical for the countries of Central and Northern Europe. Also the structure of plant production of the average Polish farm was similar to a considerable degree to that of British and German farms, while the structure of animal production resembled that of the average Hungarian farm. The conducted hierarchical agglomeration classification (according to the structure of output, ESU, total area under cultivation, output and income) permitted to include the average Polish individual farm to the class of medium-small farms from Central and Eastern Europe, which engage chiefly in the production of plants such as cereals, vegetables and flowers, but also in the production of milk and dairy goods, and in the production of pork meat.
Keywords: structure of output; plant and animal production; similarity of structures; individual farm